Tsunami Hazard Level Mapping and Evaluation of Temporary Evacuation Sites (TES) on the Palabuhanratu Coast - Rosyadah, Rani; Sutoyo; Putra, Heriansyah; Ramadhanis, Zainab (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Indonesia is highly prone to disasters due to its location at the convergence of three active tectonic plates: the Eurasian, Pacific, and Indo-Australian plates. Sukabumi Regency ranks as the second-highest risk area in the country. In the coastal region, Palabuhanratu Urban Village has the highest population density in Palabuhanratu District, reaching 6,042 people/km². The high population density in coastal areas increases the potential for casualties in the event of a tsunami. Therefore, mitigation efforts in the form of Temporary Evacuation Sites (TES) are essential across the coastal areas of Palabuhanratu District. A reassessment of the existing TES locations is necessary to evaluate their effectiveness. This study aims to identify the affected area and population under tsunami scenarios with run-up heights of 10 m, 15 m, and 20 m. Additionally, it analyzes the coverage of TES locations and the effectiveness of evacuation routes in Palabuhanratu District. The analysis is conducted using ArcGIS and QGIS software through several stages, including tsunami hazard zoning, tsunami inundation modeling, TES coverage analysis, and evacuation route optimization using network analyst tools. The results indicate that 90.6% of the coastal area in Palabuhanratu District falls into the safe category. The tsunami inundation modeling shows an affected area of 3.32 km² (run-up 10 m), 4.9 km² (run-up 15 m), and 6.1 km² (run-up 20 m). The estimated affected population for these run-up heights is 6,123, 9,348, and 12,849 people, respectively. On average, 68% of the affected population can reach a TES. A total of 68 evacuation routes were generated, with 30 routes classified as highly safe, safe, or moderate, requiring 0–20 minutes of travel time. The findings suggest that additional TES locations should be strategically placed along the coastal areas, particularly near residential zones, to improve evacuation efficiency.